THE ROLE OF "METHODS OF TEACHING SEPARATED PIECES" IN UZBEK LANGUAGE EDUCATION (Academia Science Repository, 2023)
To assist individuals desiring to benefit the worldwide work of Jehovah's Witnesses through some form of charitable giving, a brochure entitled Charitable Planning to Benefit Kingdom Service Worldwide has been prepared. A practical analysis of the methods used in the teachingof the types of b variations allocated to students of the academic lyceum is conducted. The article was purposefully implemented.